Bivalirudin or unfractionated heparin in patients with acute coronary syndromes managed invasively with and without ST elevation (MATRIX): randomised controlled trial. (27th September 2016) - Leonardi, Sergio; Frigoli, Enrico; Rothenbühler, Martina; Navarese, Eliano; Calabró, Paolo; Bellotti, Paolo; Briguori, Carlo; Ferlini, Marco; Cortese, Bernardo; Lupi, Alessandro; Lerna, Salvatore; Zavallonito-Parenti, Dennis; et al.
Abstract : Objective  To test the optimal antithrombotic regimen in patients with acute coronary syndrome. Design  Randomised controlled trial. Setting  Patients with acute coronary syndrome with and without ST segment elevation in 78 centres in Italy, the Netherlands, Spain, and Sweden. Participants  7213 patients with acute coronary syndrome and planned percutaneous coronary intervention: 4010 with ST segment elevation and 3203 without ST segment elevation. The primary study results in the overall population have been reported previously. Interventions  Patients were randomly assigned, in an open label fashion, to one of two regimens: bivalirudin with glycoprotein IIb/IIIa inhibitors restricted to procedural complications or heparin with or without glycoprotein IIb/IIIa inhibitors. Main outcome measures  Primary endpoints were the occurrence of major adverse cardiovascular events, defined as death, myocardial infarction or stroke; and net adverse clinical events, defined as major bleeding or major adverse cardiovascular events, both assessed at 30 days. Analyses were performed by the principle of intention to treat. Results  Use of a glycoprotein IIb/IIIa inhibitor in patients assigned to heparin was planned at baseline in 30.7% of patients with ST segment elevation, in 10.9% without ST segment elevation, and in no patients assigned to bivalirudin. In patients with ST segment elevation, major adverse cardiovascular events occurred in 118 (5.9%) assigned to bivalirudin and 129 (6.5%) assigned to heparin (rate ratio 0.90, 95% confidence interval 0.70 to 1.16; P=0.43), whereas net adverse clinical events occurred in 139 (7.0%) patients assigned to bivalirudin and 163 (8.2%) assigned to heparin (0.84, 0.67 to 1.05; P=0.13). In patients without ST segment elevation, major adverse cardiovascular events occurred in 253 (15.9%) assigned to bivalirudin and 262 (16.4%) assigned to heparin (0.97, 0.80 to 1.17; P=0.74), whereas net adverse clinical events occurred in 262 (16.5%) patients assigned to bivalirudin and 281 (17.6%) assigned to heparin (0.93, 0.77 to 1.12; P=0.43). Conclusions  A bivalirudin monotherapy strategy compared with heparin with or without glycoprotein IIb/IIIa inhibitors, did not result in reduced major adverse cardiovascular events or net adverse clinical events in patients with or without ST segment elevation. Trial Registration  ClinicalTrials.gov NCT01433627 .